Association between DMFT and primary headaches: a study based on the Rafsanjan cohort study - Fatemeh Ayoobi; Parvin khalili; Zahra Jamali; Sogand Esmaeil Moghaddam; Farimah Sardari; Alireza Vakilian (BMC, 2024)
Abstract Background Although primary headaches are common disorders, there is little research on the possible relationship between primary headaches and oral health (decayed, missing, and filled teeth: DMFT). The present study aims to investigate the relationship between the DMFT index and primary headaches. Method This descriptive study was performed on 8682 cases from the Rafsanjani cohort population based on the Rafsanjani cohort study (RCS) and Oral Health Branch of the Rafsanjan Cohort Study (OHBRCS). Episodic primary headache (EPH) and chronic primary headache (CPH) of RCS patients who participated in OHBRCS were studied according to their DMFT score in comparison to nonprimary headache patients. Demographic characteristics and risk factors were compared in different groups. We used crude and multiple logistic regression analyses in this study. Results The missing teeth were significantly higher in the CPH group than in the no CPH group (P < 0.001), and filled teeth were significantly higher in the EPH group than in the no EPH group (P < 0.001). In the crude model, there was a direct significant association between the prevalence of EPH and filled teeth total and > 5 filled teeth, and after adjusting for confounders, this relationship remained significant. The odds ratios of CPH were not associated with DMFT or its components in the adjusted models. Conclusion Our study found a correlation between filled teeth and EPH cases, but no correlation between CPH and DMFT or its components.